Pendampingan Pembelajaran Kolaboratif Mural Tematik bagi Siswa di SMPN 10 Kota Malang - Rohman, A. Syarifuddin; Anggrian, Mayang (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
SMPN 10 Malang is a school that implements inclusive learning, so some of its educational-inclusive programs need to be supported and optimized. In collaboration with the Fine Arts Program at Brawijaya University, SMP 10 Malang facilitates students and university students in learning fine arts through the creation of educational thematic murals. The creation of educational thematic murals is important to provide recreational learning that accommodates the educational needs of both regular and special needs students. The process of creating educational thematic murals involves teachers, 7th and 8th-grade students, and Fine Arts students from Brawijaya University, with the theme of sustainable living. The learning process uses adaptive and collaborative methods. The outcome of this activity is the creation of a sustainable lifestyle-themed mural with 9 themes across 19 sections of the school's front wall. This provides contextual, inclusive, and recreational learning activities for the “special” students of SMPN 10. Additionally, the mural serves an artistic purpose for the school environment, and art students gain a contextual learning medium.